Nonlinear Isocapacitary Concepts of Mass in 3-Manifolds with Nonnegative Scalar Curvature - Benatti, Luca; Fogagnolo, Mattia; Mazzieri, Lorenzo (Symmetry, Integrability and Geometry: Methods and Applications, 2023)
We deal with suitable nonlinear versions of Jauregui's isocapacitary mass in 3-manifolds with nonnegative scalar curvature and compact outermost minimal boundary. These masses, which depend on a parameter 1 < ≤ 2, interpolate between Jauregui's mass = 2 and Huisken's isoperimetric mass, as → 1⁺. We derive positive mass theorems for these masses under mild conditions at infinity, and we show that these masses do coincide with the ADM mass when the latter is defined. We finally work out a nonlinear potential theoretic proof of the Penrose inequality in the optimal asymptotic regime.